Hubungan Antara Kemampuan Kerja Dengan Kualitas Pelayanan Pada Tenaga Kesehatan di RS Mata Kemenkes Makassar - Siti Rahmawati; Syahruddin; Meliana Handayani; Purnamanita Syawal (RS Mata Makassar, 2026)
Work ability of health workers is one of the factors that plays an important role in improving service quality in hospitals. Work ability includes knowledge, skills, and experience in performing health services. This study aimed to determine the relationship between work ability of health workers and service quality at the Eye Hospital of the Ministry of Health Makassar. This research used a quantitative method with a cross-sectional design. Data were collected using questionnaires, while data analysis was conducted using the Spearman correlation test. The results showed that there was a significant relationship between work ability of health workers and service quality (r = 0,663; p < 0,001). The correlation was positive with a strong level of strength, indicating that better work ability of health workers tends to be associated with higher service quality. Therefore, improving work ability through training and competency development is necessary as an effort to enhance service quality in hospitals.